Training and Assistance KIP’S College Student to Develop Hard Skill and Soft Skill - Eriani, Eva; Syarifudin; Ridhwan, M (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2022)
Students who are recipients of the KIP Lecture scholarship should not only have extensive knowledgebut must also have various skills. Both hard skills are skills related to science and technology, and softskills are skills related to emotional intelligence. However, in reality, many students still do not knowor realize the importance of hard and soft skills in their lives. This community service aims to develophard and soft skills through training and mentoring. Before determining the type of activity, a needsanalysis was carried out to map the difficulties and needs of students. Furthermore, the implementationof training and mentoring is divided into three types of activities: the field of technology, the field ofwriting, and the field of self-development. After all, activities are carried out, and an evaluation is carriedout by filling out a questionnaire. So it was found that the community service program carried out bythe STAI Auliaurrasidin Tembilahan lecturer team gave a good impression so the participants wanted afollow-up program. In addition to gaining a lot of new knowledge and skills, participants can alsodevelop hard and soft skills because the activities are varied with an intense schedule.